An update on potential pharmacotherapies for cognitive impairment in bipolar disorder. (24th March 2023) - Johnson, Danica E.; McIntyre, Roger S.; Mansur, Rodrigo B.; Rosenblat, Joshua D.
ABSTRACT: Introduction: Cognitive impairment is a core feature of bipolar disorder (BD) that impedes recovery by preventing the return to optimal socio-occupational functioning and reducing quality of life. Presently, there are no efficacious treatments for cognitive impairment in BD, but many pharmacological interventions are being considered as they have the potential to target the underlying pathophysiology of the disorder. Areas covered: This review summarizes the available evidence for pharmacological interventions for cognitive impairment in bipolar disorder. We searched PubMed, MedLine, and PsycInfo from inception to December 1 st, 2022. Traditional treatments, such as lithium, anticonvulsants (lamotrigine), antipsychotics (aripiprazole, asenapine, cariprazine, lurasidone, and olanzapine), antidepressants (vortioxetine, fluoxetine, and tianeptine) and psychostimulants (modafinil), and emerging interventions, such as acetylcholinesterase inhibitors (galantamine and donepezil), dopamine agonists (pramipexole), erythropoietin, glucocorticoid receptor antagonists (mifepristone), immune modulators (infliximab, minocycline and doxycycline), ketamine, metabolic agents (insulin, metformin, and liraglutide), probiotic supplements, and Withania somnifera are discussed. Expert opinion: The investigation of interventions for cognitive impairment in BD is a relatively under-researched area. In the past, methodological pitfalls in BD cognition trials have also been a critical limiting factor. Expanding on the existing literature and identifying novel pharmacological and non-pharmacological treatments for cognitive impairment in BD should be a priority.